Estudo de incorporação de lama de alto forno em composição mássica para produção de tijolos - JESUS, Geyna Evellyn Silva de (2020)
The objective of this study was to evaluate the influence of blast furnace sludge incorporation from steelmaking activities as a mass constituent in clays for the manufacture of bricks for civil construction. The clays that were used come from a municipality called São Miguel do Guamá located in the State of Pará. They were classified into two types: one strong clay (AFO) and the other weak clay (AFR), where the AFO has more quantities. clay minerals and smaller amounts of impurities than AFR. And the blast furnace sludge, a waste from a steel mill located in the southeast of the state of Pará. The study began with the processing of clays and mud and had as a consequence the characterizations. The chemical characterization of the clays was performed by energy dispersive spectroscopy (EDS) and the residue by X-ray fluorescence (XRF), the mineralogy characterization was done by X-ray diffraction (XRD). The thermal behavior was determined by thermogravimetric analysis (TG) and (DTG). In addition, morphological analysis was also performed by optical microscopy (OM) and scanning electron microscopy (SEM). Masses with percentages of 0, 5, 10 and 15 wt% Of blast furnace sludge were prepared and, from this, specimens (CP) were molded, where they were sintered at temperatures of 750, 850 and 950 ° C. After sintering, the physical and mechanical properties of the specimens were determined as specific apparent mass, water absorption and bending stress at three points. Then, the microstructural analysis of the SEM fractures was performed. The results showed that the composition of 10wt% by weight of the residue at a temperature of 950 ° C presented the ceramic pieces with better technological values for potential use in the ceramic industries.